Peningkatan Minat Belajar Siswa dengan Online Remedial Teaching Menggunakan Google Drive - Ari Utami Nelyano (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2020)
This study aims to determine student interest in remedial learning online at SMPN.1 Tebing, so that students' interest in learning to participate in remedial activities is increasing. So that when there are programmed remedies, many students are absent for various reasons. As the solution of this study showed positive results, by holding Remedial Online learning turned out to be a solution how to attract students' learning interest so that they are complete in science and mathematics lessons, according to the authors of the results of this study 98% showed students caring and responsive with online remedial learning with use Google Drive Software and Smartphone Hardware that they have. 80% of them agree that this activity is able to give them encouragement and motivation, to find out the incomplete material, indirectly build language, science, and mathematics literacy in students, look for references to the material in cyberspace. Remedial online is a future learning solution that is easy to access and obtain wherever students are and are one of the complete independent learning for them to find information and transformation of knowledge they can.